(untitled) (Ameghiniana, 2018)
Some trace fossils can be considered direct evidence of predatory activities. In this paper we present a new nearly complete tarsometatarsus of the early Miocene diving duck Cayaoa bruneti from Gaiman Formation, and we describe predation traces distributed on its surface. The fossil presents different sets of scores attributable to attack or scavenging of Hathliacynidae metaterians. The EDAX analyses of the mark surface compared with the unaltered surface of the bone showed no significant compositional differences. This is the first direct evidence of behavioral interaction between Cayaoa bruneti and other members of the fauna of Gaiman Formation.